Where can you go on the go? An Assessment of Public Restroom Access along Transit in San Diego - Adriana Rios; Rebekah O’Donnell; Madison R. E. Swayne; Megan Welsh Carroll (Findings)
For people "on the go" like public transit riders, restroom access can be a valued amenity, especially as cities seek to curb greenhouse gas emissions by reducing auto-dependence. However, little research exists on public restroom access along transit lines. This study: 1) visualizes the distribution of available restrooms along trolley lines in San Diego, California; and 2) assesses the basic health-supportive features of available transit-adjacent restrooms. Results show low restroom availability, especially at stations with the highest volumes of riders. Results also reveal limited access and low quality of the restroom facilities that are available.